STRATEGI PROMOSI WISATA BUDAYA BERNUANSA RELIGI DI KABUPATEN MALANG - Kirom, Novita Rifaul (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
Abstract: The country of Indonesia is very beautiful and enchanting with a variety of cultures, ethnicities, customs, and religions that are owned from Sabang to Merauke. Historical background, a cool and geographical environment of various ethnicities, the development of the region, various languages are also one of the factors that add to the richness of Indonesian culture to be known in the global community. these differences provide more value for Indonesia. The uniqueness and diversity will never be extinct if it continues to be preserved by the nation's generation. As an archipelago country with various cultures and has quite a number of citizens, Indonesia will be easily known abroad.. Keywords: Keywords: Promotion strategy, culture, tourist